Sensitivity of various skinfold sites to fat deposition in adolescent daughters and their mothers - Sinha, Rashmi; Kapoor, Satwanti (Acta Biologica Szegediensis, 2007)
The present study comprised of 412 adolescent daughters at a yearly intervals from age 11 through 17 years and their mothers who volunteered as subjects. All the subjects belonged to Punjabi speaking Khatri, an endogamous population residing in Delhi, India. A set of five skinfold thickness: biceps, triceps, subscapular, suprailiac and medial calf along with body weight and stature were taken on all the subjects to report the pattern of subcutaneous fat distribution and responsiveness of different skinfold sites to fat deposition with variation in total body fat content. An increase in body mass index (bmi) with age in the present sample with a concurrent increase in the grand mean thickness (GMT) is due to relative increase in fatness. All the skinfold thicknesses, indices of fatness, profile of subcutaneous fat accumulation and sensitivity of each skinfold site showed an increasing fat deposition on trunkal region than on extremities. It was noticed that subscapular site as the most sensitive site followed by triceps and biceps towards fat deposition. The differential rate of fat deposition at various sites in different age groups explains the difference in morphological feature in them.